Dielectric Relaxation Study of Diethylene Glycol Monomethyl Ether with Aromatic Compounds Using Time Domain Reflectometry Technique : A Scientific Explanation - Maheshmalkar, P. R.; Sayyad, S. B.; Shivalkar, K. N.; Undre, P. B.; Khirade, P. W. (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
The Complex permittivity spectra e* = e'-je" of binary mixtures of Diethylene Glycol Monomethyl Ether with aromatic compounds at different temperatures have been measured in the frequency range of 10 MHz to 20 GHz using the time domain reflectometry technique. Dielectric parameters viz. dielectric constant (e0), relaxation time (t) were obtained from complex permittivity spectra using nonlinear least squares fit method. Using these parameters excess permittivity (e0E), excess inverse relaxation time (1/t)E, Bruggeman factor (fB), Kirkwood correlation factor (geff) were determined. On the basis of above parameters, intermolecular interaction and dynamics of molecules at molecular level are predicated. Study of Dielectric relaxation of binary mixture in microwave frequencies has become very important tool to get information regarding intermolecular and intramolecular interaction between mixing components.